(untitled) (Cadernos de Sociomuseologia, 2020)
This article proposes to address the importance of social museology for the development of outstanding institutions focusing on heritage, memory and history. For this, the article approaches the experience of the Living Museum of São Bento, an institution exponent in the region of Baixada Fluminense, in the State of Rio de Janeiro, which deals with such issues. The official creation of the Museum took place in 2008, through the demands of education professionals in the municipality of Duque de Caxias and its social agents, in dialogue with social museology, attributes to the Museum the role of an agent with a social function from of practices that respect cultural diversity and, in fact, integrate the local community. In this way, it becomes a social transforming agent with political, cultural and pedagogical power, which, when transforming the environment, transforms everyone. With a view to building the dimensions of the social function of museums, and taking as reference the Living Museum of São Bento itself, the article also presents the paths taken to consolidate the museology renewal movements, from the perspective of social museology and the importance of collectives for the strengthening and democratization of museums. Keywords: Social Museology; Museu Vivo do São Bento; Social Function; Museums.